2011
DOI: 10.1590/s0370-44672011000300016
|View full text |Cite
|
Sign up to set email alerts
|

Espectrocolorimetria de variedades de caulim da Jazida Ipixuna, no Estado do Pará

Abstract: ResumoVariedades de minério de caulim amostradas em uma jazida sedimentar no Estado do Pará foram beneficiadas em planta-piloto para estudos de espectrocolorimetria que possibilitassem a criação de uma ferramenta de apoio operacional à lavra e ao beneficiamento. Jazidas como esta contêm blocos com variações texturais e mineralógicas, as quais definem os blocos de minério com potencial para beneficiamento. A tomada de decisão depende, inicialmente, da análise subjetiva da cor do minério: blocos com cores averme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
1
Order By: Relevance
“…According to Sabedot et al (2011), chemical analysis performed in four samples showed similar titanium content, which can be interpreted as the e ect of the material mixture during sample preparation, or may suggest that Ti was present in other phases of secondary minerals such as goethite. e latter is less plausible due to the geochemical properties of Ti, which has little mobility in a supergene environment and forms independent phases.…”
Section: Red Contaminantsmentioning
confidence: 94%
See 1 more Smart Citation
“…According to Sabedot et al (2011), chemical analysis performed in four samples showed similar titanium content, which can be interpreted as the e ect of the material mixture during sample preparation, or may suggest that Ti was present in other phases of secondary minerals such as goethite. e latter is less plausible due to the geochemical properties of Ti, which has little mobility in a supergene environment and forms independent phases.…”
Section: Red Contaminantsmentioning
confidence: 94%
“…Research carried out by Sabedot et al (2011) indicated that the Ipixuna Mine deposit is formed by run-of-mine (ROM) material blocks with low brightness (59.4%) and high yellowness (15.5%) because of high levels of Fe 2 O 3 and TiO 2 . However, a er magnetic separation and chemical bleaching processes, some ROM blocks produced a nal raw material with values of 87.4% for brightness and 6.8% for yellowness.…”
Section: Introductionmentioning
confidence: 99%
“…Produtos e rejeitos decorrentes foram analisados quanto as suas características físicas, químicas, mineralógicas e colorimétricas. Sabedot et al (2011) definiram, com base nos resultados colorimétricos, sete grupos espectrofotométricos de minério ROM e indicaram os grupos adequados e inadequados à produção de um produto final com qualidade para a indústria de papel, bem como sugeriram situações de blendagens entre os grupos. No atual estudo, acrescentam-se informações sobre as características mineralógicas dos grupos espectrofotométricos e que interferem no beneficiamento mineral.…”
Section: Introductionunclassified